If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32x + 64 = -1x + 2 Reorder the terms: 64 + 32x = -1x + 2 Reorder the terms: 64 + 32x = 2 + -1x Solving 64 + 32x = 2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 64 + 32x + x = 2 + -1x + x Combine like terms: 32x + x = 33x 64 + 33x = 2 + -1x + x Combine like terms: -1x + x = 0 64 + 33x = 2 + 0 64 + 33x = 2 Add '-64' to each side of the equation. 64 + -64 + 33x = 2 + -64 Combine like terms: 64 + -64 = 0 0 + 33x = 2 + -64 33x = 2 + -64 Combine like terms: 2 + -64 = -62 33x = -62 Divide each side by '33'. x = -1.878787879 Simplifying x = -1.878787879
| x^2-11x+28/2x=0 | | 3y^3+23y^2-8y=0 | | 2x=5.75+7y | | 120/115=109.2/p | | -9+6-(-2)=4 | | 3x-2*-1=14 | | 8x^2+52x-28=0 | | -80-(-15)= | | 7(6+x)=-28 | | 3(2a-7)+2a=-4(3a+2)+27 | | p=6+-2q | | -80-(15)= | | 40/-5 | | (5x^2)(2x^5)= | | 120/350=304.8/a | | 32-(-6)= | | -5/9*(6/8) | | 12-4x/3=x/6 | | -(-1)^2+3*(-1)-5*(-1)*3+1/3*(-1)*9 | | -9-(-13)= | | -6(7-7n)=28+7n | | 14x-9=4x+13 | | 4+3(x-6)=6-3(x+3) | | 5b+(11-3b)+23= | | 15r*2+32r-7=0 | | -8+-13= | | 5z+6-2z=51-2z | | x^2+4x^2+36x^2=4x^2+16x^2 | | -2n=-18 | | x^3+5X-3=0 | | -12+4x=7(2x+4) | | 3(5x-6)+7(10-x)= |